Reimagining Democracy - Farrell, David M.; Suiter, Jane (Cornell University Press, 2023)
The Lawrence and Lynne Brown Democracy Medal, presented by the McCourtney Institute for Democracy at Penn State, recognizes outstanding individuals, groups, and organizations that produce innovations to further democracy in the United States or around the world. 2019 Brown Democracy Medal winners David M. Farrell and Jane Suiter are co-leads on the Irish Citizens' Assembly Project, which has transformed Irish politics over the past decade. The project started in 2011 and led to a series of significant policy decisions, including successful referenda on abortion and marriage equality. Thanks to generous funding from The Pennsylvania State University, the ebook editions of this book are available as Open Access (OA) volumes, available from Cornell Open (cornellpress.cornell.edu/cornell-open) and other Open Access repositories.